Perlaksanaan ISO 14000 dan kesannya terhadap peningkatan kos di kalangan organisasi di Malaysia - Kadir Arifin; Jamaluddin Md. Jahi; Abd Rahim Md Nor (Environmental Management Society, Malaysia, 2006)
ISO 14000 is seen as a mechanism towards a more systematic and better ways of environmental control compared with environmental control instruments introduced so far. When fully implemented, it is expected to streamline efforts to control the environment in each country in a global framework. This standardisation should be practical, beneficial and can be implemented by all organisations regardless of their sizes, both in the manufacturing and service sectors, worldwide. For any organisation, the benefits of implementing ISO 14000 includes enhancement of organisation’s image, better local and global competitiveness, energy and resource savings, and the ability to avoid legal actions. Despite the benefits, the implementation of ISO 14000 is limited by cost constraint. Many organisations implemented it half-way due to the huge costs involved. There are also organisations which delay or slow in the implementation due to costs. If the costs are too high, it will not financially benefit the organisations. This paper examines aspects of cost increases in the implementation of this standardisation among 26 organisations in Malaysia